Clinical reporting following the quantification of cerebrospinal fluid biomarkers in Alzheimer's disease: An international overview. (31st December 2021) - Delaby, Constance; Teunissen, Charlotte E.; Blennow, Kaj; Alcolea, Daniel; Arisi, Ivan; Amar, Elodie Bouaziz; Beaume, Anne; Bedel, Aurélie; Bellomo, Giovanni; Bigot‐Corbel, Edith; Bjerke, Maria; Blanc, Marie‐Céline; et al.
Abstract: Background: The quantification of cerebrospinal fluid (CSF) biomarkers (Amyloid beta peptides [Aß1‐40 and Aß1‐42], t‐tau and p‐tau(181)) is progressively implemented in specialized laboratories as an aid for the multidisciplinary diagnosis of Alzheimer's disease (AD). There is however a diversity of practices between centers related to pre‐analytical and analytical conditions, the calculation of ratios between analytes, the applied cut‐off, or the use of interpretation scales. Finally, for the same biochemical profile, the interpretation and reporting of results may differ from one center to another, which may raise questions about the commutability of the tests. So far, no consensus has been reached between the different laboratories involved to define the most appropriate conclusions/comments based on the profile of the quantified biomarkers. This work is an essential step towards a consensual harmonization of clinical reporting after CSF analysis in the context of AD diagnosis, as advocated by the "Biofluid Based Biomarkers PIA" working group of the Alzheimer's Association. Method: We obtained, by means of a questionnaire, a description of the pre‐analytical and analytical protocols and examples of reporting from 40 centers located in 15 countries, i.e. in the majority of countries that have implemented clinical CSF tests for the diagnosis of AD. We then adopted a consensus approach to propose harmonized comments corresponding to different AD CSF biomarker profiles observed in patients. Result: Pre‐analytical procedures were very similar, among the centers. Regarding the analytical part, more than 88% of the laboratories use automatized immunoassays and more than 83% measure Aß1‐40 and compute the Aß1‐42/Aß1‐40 ratio, in addition to the three core biomarkers (Aß1‐42, t‐tau and p‐tau(181)). The cut‐off values of biomarkers used by the different laboratories are widely dispersed. Delay before sending back the results is lower than 1 week in more than 34% of the laboratories. Conclusion: Our results highlight the state of the art in terms of clinical CSF analysis in the context of AD. Harmonization of clinical reporting between different centers could benefit AD care, prevention and treatment strategies, as a common terminology will allow a better assessment of the prevalence of AD and the contribution of biochemical biomarkers to its diagnosis.